Metronidazole-induced cerebellar toxicity - Amit Agarwal; Sangam Kanekar; Shyam Sabat; Krishnamurthy Thamburaj (MDPI AG, 2016)
Metronidazole is a very common antibacterial and antiprotozoal with wide usage across the globe, including the least developed countries. It is generally well-tolerated with a low incidence of serious side-effects. Neurological toxicity is fairly common with this drug, however majority of these are peripheral neuropathy with very few cases of central nervous toxicity reported. We report the imaging findings in two patients with cerebellar dysfunction after Metronidazole usage. Signal changes in the dentate and red nucleus were seen on magnetic resonance imaging in these patients. Most of the cases reported in literature reported similar findings, suggesting high predilection for the dentate nucleus in metronidazole induced encephalopathy.